The Challenge of Urogenital Tuberculosis Diagnosis in Elderly Patients - Seabra, Carolina; Silva, Ana Filipa; Duro, Raquel; Paupério, André; Fagundes, Vitor (Brazilian Journal of Case Reports, 2025)
Recurrent urinary tract infections (UTIs) in elderly patients with comorbidities can present diagnostic challenges. Extrapulmonary tuberculosis, particularly urogenital tuberculosis, is a rare but important cause of persistent genitourinary symptoms. We describe the case of an 83-year-old female with hypertension, diabetes, chronic kidney disease, and obesity who was repeatedly hospitalized for UTIs. In December 2023, she presented with progressive weakness, suprapubic pain, and altered urine despite prior antibiotic treatment. Imaging showed important bilateral pyelocalyceal dilation. She was diagnosed with urinary retention and remained catheterized. In February 2024, the patient was readmitted with multi-organ dysfunction, and Mycobacterium tuberculosis was eventually isolated from a urine culture. Despite being referred for treatment, the patient died. This case emphasizes: 1) the need to consider urogenital tuberculosis in elderly patients with recurrent UTIs, particularly in regions where tuberculosis is prevalent; 2) the importance of early diagnosis for appropriate and timely treatment, fundamental for a favorable outcome of a treatable disease. This case highlights the importance of implementing structured diagnostic protocols and educational initiatives to raise awareness of urogenital tuberculosis in elderly patients. Clinicians should prioritize early use of diagnostic tools like urine cultures for Mycobacterium tuberculosis and nucleic acid amplification tests, particularly in high-risk populations, to mitigate diagnostic delays and improve patient outcomes.